2021
DOI: 10.1007/s40134-021-00382-6
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Ultrasound: Is Still a Valid Tool?

Abstract: Purpose of Review The main purpose of this paper review is to highlight the latest ultrasound (US) imaging technologies of the prostate gland, an organ increasingly at the center of attention in the field of oncological diseases of the male sex, which needs a 360° evaluation in order to obtain tailored therapeutic planning. Specialist urological evaluation is designated for this purpose, together with integrated prostate imaging which currently tends to focus more and more on the use of US imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The bulk of modern ultrasound machines are equipped with ultrasonic technology capable of scanning microbubble contrast agents. In addition, because cancers are often associated with increased blood flow, targeted prostate biopsies may be conducted [25]. A study of 1776 males scheduled for their first or subsequent biopsy showed that collecting five targeted biopsy cores from hypervascular areas in the peripheral zone resulted in a slightly better detection rate (26.8%) than doing ten systematic core biopsies (23.1%) [26].…”
Section: Transrectal Ultrasound (Trus)mentioning
confidence: 99%
“…The bulk of modern ultrasound machines are equipped with ultrasonic technology capable of scanning microbubble contrast agents. In addition, because cancers are often associated with increased blood flow, targeted prostate biopsies may be conducted [25]. A study of 1776 males scheduled for their first or subsequent biopsy showed that collecting five targeted biopsy cores from hypervascular areas in the peripheral zone resulted in a slightly better detection rate (26.8%) than doing ten systematic core biopsies (23.1%) [26].…”
Section: Transrectal Ultrasound (Trus)mentioning
confidence: 99%